Pengaruh Work Life Balance Dan Brunout Terhadap Produktivitas Kerja Karyawan PT. Indomarco Adi Prima Surabaya - Febriani Selvia Devi Safitri; Agus Frianto (BIMA : Journal of Business and Innovation Management, 2021)
The purpose of this study was to examine and analyze effect of work life balance and burnout on the work productivity of the employees of PT. Indomarco Adi Prima Surabaya. The sample used in this study is the entire population of 60 employees. The data collection technique  was  carried  out  by observing,  distributing  questionnaires,  and  conducting interviews with several respondents. The analysis technique in this study is multiple linear analysis with the SPSS version 23 program. The findings in this study are that work life balance has a positive and significant effect on work productivity, and burnout has a negative and insignificant effect on work productivity. The suggestion that can be put forward in this research is that PT. Indomarco Adi Prima Surabaya can be able to maintain policies that can facilitate the employees in increasing work life balance and trying not to make employees experience higher burnout. Keywords: Burnout; Work Life Balance; Work Productivity